Health and safety leadership: A study of employee perceptions and company leader responses in New Zealand's electricity supply industry. Issue 4 (31st October 2019) - Börner, Heidi Elizabeth; Lassowski, Sandra
Abstract : Purpose: Based on the research findings the authors derive propositions for further research to explore the role of safety and ethical leadership in enhancing health and safety performance within New Zealand companies. The paper aims to discuss this issue. Design/methodology/approach: Based on quantitative and qualitative health and safety data collected by Börner in New Zealand and analysed in the (unpublished) Master Thesis of Lassowski "Supporting Aspects of Organisational culture on Occupational Health and Safety" (2014) the authors will examine in this paper the responses of company governance and senior leadership to reports made from front-line staff about their perception of the safety culture and (potential) threats to health and safety. Findings: The data indicate that company governance and senior leadership are sometimes reluctant to give adequate responses to employee reporting and fail to take effective measures to protect people and the business. Research limitations/implications: Directors and senior leaders need to be vigilant that the company systems remain compliant with Health and Safety legislation and are aligned with best practices in the sector/organisation. Reports from employees using company systems on a daily basis are vital to assure that those systems work as they should, and that action can be taken when (potential) threats to health and safety are reported. Originality/value: The workplace has a significant influence on injury, illness, fatalities and threats to environmental, community and individual wellbeing and this influence can be positive or negative. The research explores the link between the ethics of organisational leadership and its influence on workplace health and safety climate and outcomes.